Metacognição, letramento e compreensão do texto acadêmico: reflexões sobre uma experiência de leitura com alunos de um curso superior tecnológico - Egito, Niedja Balbino do (2019)
As reading is the main activity used by higher education students to learn and also the most encouraged one by teachers, the quality of the reading comprehension, demonstrated mainly in the first period of graduation, has generated discussions around the level of literacy built throughout the students' lives. This research is based on the search for an understanding of the perceptions, reactions and reflections of the students of a technological higher education course on the proposed paths in a didactic experience to solve the lags of their academic literacy. Through this experience, which is eminently metacognitive, we aim to understand how the participating students have developed their awareness regarding the use of cognitive and metacognitive strategies to facilitate the reading comprehension of academic texts. Thus, we are based on the perspective of reading as a sociocognitive process, with emphasis on metacognitive monitoring which has been the theoretical basis for reading at the university level and in the courses developed to improve study strategies (VEENMAN, VAN HOUT-WOLTERS; AFFLERBACH, 2006). The sociocognitive approach to reading, besides seeing metacognition as the conscious monitoring of study strategies for constructing the meaning of the read text, takes into consideration the social aspect, which is manifested by the social functions fulfilled through reading. In addition to this theory, we benefit from the theoretical basis of literacy, because we understand reading as a complex process that can not be defined by a single approach. Our research reflects on the Academic Literacy of students from the first module (2016.2) of the Superior Course of Technology in Environmental Management from the Federal Institute of Alagoas, Campus Marechal Deodoro, focusing on reading comprehension of the academic text. As for the methodology, this is a qualitative research of an ethnographic nature, more specifically an ethnographic case study, where, within a school semester, 10 study sessions were carried out, structured with revision of some linguistic concepts and reading activities, especially application of cloze tests. After conducting the tests with all the participants, we selected some students to make reading verbal protocols in order to obtain data for analysis of students' performance in these tests. We then arrived at reading experiences with academic articles and finished the period of the experiment with the application of a final evaluation questionnaire to verify the students' reflections about the work performed and the possible benefits of that for the development of their reading comprehension. The results of the research revealed that the participants supported the experience taking into account the development of the readind of the academic text, by understanding the importance of using metacognitive strategies for reading comprehension.